Analisis Dampak Lingkungan Belajar terhadap Prestasi Akademik Siswa di SMPN 3 Tarutung - Evi Vania SIbarani; Irma Arda Shafa Siregar; Laurentina Siahaan; Septy Anita Br Gultom; Vetra Pasaribu (Universitas Insan Budi Utomo, 2024)
This research aims to analyze and describe the impact of the learning environment on student academic achievement. This research uses a descriptive approach by conducting analysis and studies on primary data sources and secondary data sources related to the learning environment and student academic achievement at school. Data analysis was carried out by paying attention to qualitative and quantitative data to obtain an overview of the impact of the learning environment on student academic achievement. The research results show that the physical environment has an impact on student academic achievement. A physical environment that is conducive, comfortable and enjoyable can make students more motivated to learn. Furthermore, the results of the analysis also show that the social environment such as interactions between students and students, students and teachers, students and parents have an impact on students' academic achievement. Thus, to improve the academic achievement of students at school, efforts are needed that lead to improving the quality of the learning environment.